Analysis of the Effect of Ct Angiography Combined with Three Tests, Mmp-9 and Paf, On the Assessment of Postoperative Vascular Stenosis in Acute Coronary Syndrome - Sun, Jia; Gao, Yiling; Ma, Jing; Zhu, Minghui; Li, Kefei; Hou, Yiyong; Xie, Chunqiao; Zhang, Huang (Journal of Medical Biochemistry, 2025)
Background: Acute Coronary Syndrome (ACS) is a very common cardiovascular disease in clinical practice with a very high risk of death. In this study, we observed the effectiveness of CT angiography (CTA), Matrix metalloproteinase-9 (MMP-9) amd Platelet activating factor (PAF) in the assessment of ACS.Materials and Methods: A total of 124 patients with ACS admitted to our hospital from June 2022 to March 2024 were enrolled as study subjects. All study subjects were examined by Coronary angiography (CAG) and CTA. To compare the detection rate of ACS by CAG and CTA, and the difference in effectiveness in assessing coronary plaque stenosis and plaque calcification. In addition, the levels of MMP-9 and PAF were detected in the patients to analyze their relationship with the degree of stenosis and plaque grade.Subsequently, the effect of the three combined tests, CTA, MMP-9 and PAF, was analyzed for the assessment of postoperative vessel restenosis. Finally, we analyzed the factors associated with poor CTA image quality.Results: There was no difference in the effectiveness of CTA in detecting ACS, assessing coronary plaque stenosis and plaque calcification compared with CAG (P>0.05). There was a positive correlation between MMP-9, PAF and the degree of coronary stenosis and plaque severity (P
Keywords: Acute coronary syndrome; CT angiography; Coronary angiography; MMP-9; PAF